2021
DOI: 10.1016/j.patter.2021.100362
|View full text |Cite
|
Sign up to set email alerts
|

Creating ethics guidelines for artificial intelligence and big data analytics customers: The case of the consumer European insurance market

Abstract: Summary The European Union (EU) has a strong reputation and track record for the development of guidelines for the ethical use of artificial intelligence (AI) generally. In this paper, we discuss the development of an AI and ethical framework by the European Insurance and Occupational Pensions Authority (EIOPA), for the European insurance market. EIOPA's earlier report on big data analytics (EIOPA, 2019) provided a foundation to analyze the complex range of issues associated with AI being deployed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 78 publications
2
12
1
Order By: Relevance
“…Based on their findings, it was discovered that there is a significant correlation between the reduced rate of accidents and the effectiveness of the AES system with the value of Pearson correlation of 0.78 which indicates a high positive strong relationship between the AES system and reducing road accidents and fatalities. This study's finding corroborated Mullins et al (2021) who found the same relationship between AES and reducing road fatalities. Thus, this study successfully added to the literature on implementing the AES system by strengthening the model of positive correlation between reducing road accidents and the effectiveness of the AES system.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on their findings, it was discovered that there is a significant correlation between the reduced rate of accidents and the effectiveness of the AES system with the value of Pearson correlation of 0.78 which indicates a high positive strong relationship between the AES system and reducing road accidents and fatalities. This study's finding corroborated Mullins et al (2021) who found the same relationship between AES and reducing road fatalities. Thus, this study successfully added to the literature on implementing the AES system by strengthening the model of positive correlation between reducing road accidents and the effectiveness of the AES system.…”
Section: Discussionsupporting
confidence: 89%
“…A cross-sectional methodology using the questionnaires as the instrument was carried out in gathering data at a single point at a time. The benefit of this method is that it allows the researchers to establish a comparison of different variables at the same time (Mullins et al, 2021). In this study, the data were collected from Malaysian drivers who used highways where the AES system was installed and monitored by RTD and PLUS.…”
Section: Methodsmentioning
confidence: 99%
“…The regulatory context is primarily concerned with GDPR requirements for handling complex and detailed personal customer data. The ethical framework is now an integral component of the regulatory and market environment and include difficult issues such as transparency and explainability of complex algorithms, bias, and fairness [26].…”
Section: Research Framework: Behavioural Insurance Business Model And...mentioning
confidence: 99%
“…At the same time, Mullins' study demonstrated that the EU insurance industry, represented by the European Insurance and Occupational Pensions Authority had developed an ethical framework for artificial intelligence for the European insurance market (EIOPA, 2021). EIOPA's work has provided findings on big data analytics as a basis for analyzing the complex set of issues associated with using AI in insurance applications in all aspects of the insurance value chain in terms of ethics (Mullins, Holland, & Cunneen, 2021). A comparative study between the laws on insurance, the fight against discrimination, and the protection of data, whether they concern health, rental, and car insurance in Switzerland and the U.S./California systems, showed that big data plays a role in the individualization of insurance contracts (Thouvenin, Suter, George, & Weber, 2019).…”
Section: Introductionmentioning
confidence: 99%